2002
DOI: 10.1046/j.1468-2982.2002.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Tanacetum Parthenium (Feverfew) in Migraine Prophylaxis—a Double-Blind, Multicentre, Randomized Placebo-Controlled Dose-Response Study

Abstract: Tanacetum parthenium (feverfew), is a well-known herb for the prophylactic treatment of migraine. The primary objective was to show a dose-response of a new stable extract (MIG-99) reproducibly manufactured with supercritical CO2 from feverfew (T. parthenium). Furthermore, the study should provide data on the safety and tolerability of MIG-99. In a randomized, double-blind, multicentre, controlled trial with an adaptive design, the clinical efficacy and safety of three dosages of MIG-99 (2.08 mg; 6.25 mg; 18.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
0
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(99 citation statements)
references
References 11 publications
3
88
0
8
Order By: Relevance
“…In some previous clinical trials, the effect of feverfew as a migraine prophylaxis was studied (10,11). In one study in Germany, the results indicated that the extract of feverfew with a dosage of three capsules of 6.25 mg per day reduced the migraine attacks per month (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some previous clinical trials, the effect of feverfew as a migraine prophylaxis was studied (10,11). In one study in Germany, the results indicated that the extract of feverfew with a dosage of three capsules of 6.25 mg per day reduced the migraine attacks per month (11).…”
Section: Discussionmentioning
confidence: 99%
“…In one study in Germany, the results indicated that the extract of feverfew with a dosage of three capsules of 6.25 mg per day reduced the migraine attacks per month (11). In a clinical trial, 72 migraine patients received dried feverfew leaves (82 mg) or placebo per day for four months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays it is a recommended therapeutic treatment for migraine prophylaxis (Khan et al, 2003). Although the pathophysiology of migraine is not yet fully understood, its symptoms are reported by 15% of females and 6% of males in the adult age, from 35 to 45 years (Pfaffenrath, 2002). Clinical trials have demonstrated the high effectiveness of feverfew against headache and other symptoms linked to migraine (Palevith, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used feverfew extracts trigger the release of serotonin (5-HT) from platelets, thus inducing a wide variety of aggregation agents (Pfaffenrath et al, 2002). The effi cacy of the extract in migraine prophylaxis was also assessed in randomized, placebo-controlled, double-blind and cross-over clinical studies (Gruenwald et al, 2000).…”
Section: Introductionmentioning
confidence: 99%